Influence of the incorporation of TiO2 nanotubes in a polycrystalline zirconia: synthesis of nanotubes, surface characterization and bond strength - Santos, Angélica Feltrin dos (2017)
Despite numerous advantages such as high strength, cementing zirconia is still critical. In the present study TiO2 nanotubes were synthesized and applied over zirconia surface. This surface was characterized and after that the bond strength test was conducted to a resin cement. TiO2 nanotubes were produced by alkaline synthesis, mixed with isopropyl alcohol (50 wt%) and applied on pre-sintered zirconia slices (IPS e.max ZirCAD). The ceramics were sintered and surfaces were characterized by confocal laser microscopy, scanning electron microscopy (SEM) and EDS analysis. For the bond strength, six groups (n = 16) were evaluated: 1) without application of TiO2 and Single Bond Universal; 2) with the application of TiO2 nanotubes and Single Bond Universal; 3) without application of TiO2 nanotubes and Z-prime; 4) with application of TiO2 nanotubes and Z-prime; 5) without application of TiO2 and Signum Zirconia Bond; 6) with application of TiO2 and Signum Zirconia Bond. After sintering, resin cement (RelyX Ultimate) cylinders with diameter of 1.40 mm and 1 mm in height were prepared and light cured for 40 s. The specimens were stored for 30 days in distilled water at 37°C and submitted to shear test. The nanotubes were incorporated in the zirconia surface and the EDS analysis has confirmed that the nanoagglomerates were composed of TiO2. The shear bond strength showed there was significant statistical difference among the analyzed groups. There was no significant statistical difference with the application of the nanotubes regardless of the analyzed group. It may be concluded that it was possible to incorporate nanotubes to the zirconia surfaces, however this incorporation did not improve the bond strength.